2018
DOI: 10.1088/1361-6595/aadb60
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of CO2 plasmas under non-equilibrium conditions. II. Input of vibrational energy

Abstract: This is the second of two papers presenting the study of vibrational energy exchanges in nonequilibrium CO 2 plasmas in low-excitation conditions. The companion paper addresses a theoretical and experimental investigation of the time relaxation of ∼70 individual vibrational levels of ground-state CO X 2 1 S + ( )molecules during the afterglow of a pulsed DC glow discharge, operating at pressures of a few Torr and discharge currents around 50mA, where the rate coefficients for vibration-translation (V-T) and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
141
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(154 citation statements)
references
References 37 publications
13
141
0
Order By: Relevance
“…In the past decade, many papers, both experimental (e.g., Silva et al, 2014Silva et al, , 2017Klarenaar et al, 2017Klarenaar et al, , 2018Klarenaar et al, , 2019Stewig et al, 2020;Terraz et al, 2020;van den Bekerom et al, 2020) and computational (e.g., Bogaerts, 2014, 2015;Pietanza et al, 2015Pietanza et al, , 2017aPietanza et al, ,b, 2018aPietanza et al, ,b, 2020Bogaerts, 2016, 2018;Capitelli et al, 2017, Heijkers andGrofulović et al, 2018;Silva et al, 2018;Bogaerts, 2018, 2019;Kotov and Koelman, 2019;Terraz et al, 2020), focused on the role of the vibrational kinetics in plasmas, but mainly at low pressure conditions (few mbar up to a few hundred mbar). Most of these studies revealed the importance of the vibrational kinetics at specific conditions (low gas temperature, low pressure) and their contribution to a high energy efficiency.…”
Section: Different Dissociation Mechanisms In Different Plasma Typesmentioning
confidence: 99%
“…In the past decade, many papers, both experimental (e.g., Silva et al, 2014Silva et al, , 2017Klarenaar et al, 2017Klarenaar et al, , 2018Klarenaar et al, , 2019Stewig et al, 2020;Terraz et al, 2020;van den Bekerom et al, 2020) and computational (e.g., Bogaerts, 2014, 2015;Pietanza et al, 2015Pietanza et al, , 2017aPietanza et al, ,b, 2018aPietanza et al, ,b, 2020Bogaerts, 2016, 2018;Capitelli et al, 2017, Heijkers andGrofulović et al, 2018;Silva et al, 2018;Bogaerts, 2018, 2019;Kotov and Koelman, 2019;Terraz et al, 2020), focused on the role of the vibrational kinetics in plasmas, but mainly at low pressure conditions (few mbar up to a few hundred mbar). Most of these studies revealed the importance of the vibrational kinetics at specific conditions (low gas temperature, low pressure) and their contribution to a high energy efficiency.…”
Section: Different Dissociation Mechanisms In Different Plasma Typesmentioning
confidence: 99%
“…These distributions are typical characteristics of glow discharge, [ 28 ] indicating that the mode of CO 2 discharge is glow discharge. It is worth noting that the maximum electron density at the peak time of discharge reached about 4.37 × 10 16 m −3 under the conditions of our paper, whereas R. Grofulović et al [ 40 ] studied the CO 2 glow discharge at 5 Torr by applying DC pulse voltage and obtained an electron density of about 8 × 10 15 m −3 . Electrons participate in the excitation, ionization, dissociation, and attachment reactions of CO 2 , such as reactions E3–E14 in this paper, and higher electron density will lead to higher reaction rates of these reactions, which will promote the decomposition of CO 2 .…”
Section: Resultsmentioning
confidence: 53%
“…The insertion of the complicated kinetics of CO in the corresponding kinetics of CO 2 will elucidate the role of CO processes in affecting eedf and vdf of the reacting CO 2 mixture when the dissociation of CO 2 is larger than 10%. In doing so one should also try to develop simplified models able to reduce the number of components as well as to insert analytical forms of vdf for describing the actual vibrational distributions of the different components (Colonna et al, 1999, 2006; Grofulovic et al, 2018; Macdonald et al, 2018).…”
Section: Discussionmentioning
confidence: 99%